ANALYSIS OF STRUCTURE, BEHAVIOR AND PERFORMANCE OF THE SEAWEED DODOL AGROINDUSTRY MARKET IN LEKOK DISTRICT, PASURUAN REGENCY - Satria Fathan Abror (Agripreneur : Jurnal Pertanian Agribisnis, 2022)
This study aims to analyze the structure, behavior and performance of the seaweed dodol agro-industry market. The amounts of respondents used are 9 companies in Pasuruan regency. The data analysis methods used are descriptive and quantitative analysis. The descriptive analysis is used to determine the market structure includes the level of product differentiation, market out and in obstructions and the level of market knowledge also market behavior determining includes price determining policy, the system of market organization and marketing functions. The quantitative analysis is used to determine the degree of market concentration that is market segment measurement. For market performance, market margin analysis and profit analysis are used. The result of this research shows that there is a close relationship between the structure, the behavior, and the performance of seaweed dodol agro industry market. It can be seen from the relationship of those three components in dynamic system. The market structure influences the behavior, and both of them influence the market performance, and so the market performance that influences the behavior and the structure of market. The structure of seaweed dodol agro industry market in Pasuruan regency belongs to monopolistic market. The characteristic of this structure is 10-20% market segment. The product differentiation has been done by each dodol seaweed producers, as well as in quality, weight and the packaging. The market out and in obstructions are big and complex enough which consist of investation capital, production cost, and local government policy. Market information is easy to get, but it is not transparent, comes from mass media, agent, retailer, and consumers about the product price, potencial location to be market, and material location.